1993
DOI: 10.1016/0014-5793(93)80051-u
|View full text |Cite
|
Sign up to set email alerts
|

Sulfhydryl oxidation induces rapid and reversible closure of the ATP‐regulated K+ channel in the pancreatic β‐cell

Abstract: Effects of sulfhydryl modification on the ATP regulated K' channel (K,,, channel) in the pancreatic B-cell were studied, using the patch clamp technique. Application of the sulfhydryl oxidizing agents thimerosal and [ 18,191.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
44
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 40 publications
7
44
0
1
Order By: Relevance
“…5,6,9) However, an additional factor may also be involved in this antiarrhythmia. Various studies have shown that both thimerosal [15][16][17] and pinacidil 32,33) induce coronary vasodilation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6,9) However, an additional factor may also be involved in this antiarrhythmia. Various studies have shown that both thimerosal [15][16][17] and pinacidil 32,33) induce coronary vasodilation.…”
Section: Discussionmentioning
confidence: 99%
“…2) ATP-sensitive K + channels (K-ATP channels) in skeletal muscle, 3,4) heart lines [6][7][8] are closed by thiol-oxidizing reagents, an effect that is in general reversed by the disulphide bond reducing agent 1,4-dithiothreitol (DTT). This modulation of K-ATP channel activity by thiol oxidation is of particular interest in heart and skeletal muscle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism by which PN alters ATPsensitive channels is not understood [82,154], it is unlikely that the oxidant properties of PN are involved since oxidants have been shown to reduce ATP-sensitive potassium channel activity [206,207]. Moreover, PN mediate vasodilator responses have been shown to be markedly attenuated by the ATP-sensitive potassium channel blocker, glibenclamide [208], but are not attenuated by L-penicillamine, in doses that can reduce the vasodilator responses to L-Snitrosocysteine, a S-nitrosothiol [163].…”
Section: Vasorelaxant Properties Of Peroxyni-tritementioning
confidence: 99%
“…This process effectively protects the cell from oxidative damage. Typically, GSSG is then converted to GSH via glutathione reductase or effluxed from the cell and degraded by extracellular-glutamyl transpeptidase [14,15] . The oxidation state and intracellular concentration of glutathione are therefore useful indicators of oxidative stress in cells.…”
Section: Introductionmentioning
confidence: 99%